PKCθ and HIV-1 Transcriptional Regulator Tat Co-exist at the LTR Promoter in CD4+ T Cells - López-Huertas, María Rosa; Li, Jasmine; Zafar, Anjum; Rodríguez-Mora, Sara; García-Domínguez, Carlota; Mateos, Elena; Alcamí, José; Rao, Sudha; Coiras, Mayte (Frontiers in Immunology, 2016)
PKCtheta is essential for the activation of CD4+ T cells. Upon TCR/CD28 stimulation, PKCtheta is phosphorylated and migrates to the immunological synapse, inducing the activation of cellular transcription factors such as NF-kB and kinases as ERK that are critical for HIV-1 replication. We previously demonstrated that PKCtheta is also necessary for HIV-1 replication but the precise mechanism is unknown. Efficient HIV-1 transcription and elongation is absolutely dependent on the synergy between NF-kB and the viral regulator Tat. Tat exerts its function by binding a RNA stem-loop structure proximal to the viral mRNA cap site termed TAR. Besides, due to its effect on cellular metabolic pathways, Tat causes profound changes in infected CD4+ T cells such as the activation of NF-kB and ERK. We hypothesized that the aberrant up-regulation of Tat-mediated activation of NF-kB and ERK occurred through PKCtheta signaling. In fact, Jurkat TetOff cells with stable and doxycycline-repressible expression of Tat (Jurkat-Tat) expressed high levels of mRNA for PKCtheta. In these cells, PKCtheta located at the plasma membrane was phosphorylated at T538 residue in undivided cells, in the absence of stimulation. Treatment with doxycycline inhibited PKCtheta phosphorylation in Jurkat-Tat, suggesting that Tat expression was directly related to the activation of PKCtheta. Both NF-kB and Ras/Raf/MEK/ERK signaling pathway were significantly activated in Jurkat-Tat cells, and this correlated with high transactivation of HIV-1 LTR promoter. RNA interference for PKCtheta inhibited NF-kB and ERK activity, as well as LTR-mediated transactivation even in the presence of Tat. In addition to Tat-mediated activation of PKCtheta in the cytosol, we demonstrated by sequential ChIP that Tat and PKCtheta coexisted in the same complex bound at the HIV-1 LTR promoter, specifically at the region containing TAR loop. In conclusion, PKCtheta-Tat interaction seemed to be essential for HIV-1 replication in CD4+ T cells and could be used as a therapeutic target.